2014
DOI: 10.1142/s0219891614500143
|View full text |Cite
|
Sign up to set email alerts
|

A counterexample to well-posedness of entropy solutions to the compressible Euler system

Abstract: We consider entropy solutions to the Cauchy problem for the isentropic compressible Euler equations in the spatially periodic case. In more than one space dimension, the methods developed by De Lellis-Szekelyhidi enable us to show here failure of uniqueness on a finite time-interval for entropy solutions starting from any continuously differentiable initial density and suitably constructed bounded initial linear momenta

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
153
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 127 publications
(156 citation statements)
references
References 21 publications
2
153
0
Order By: Relevance
“…Similarly, r need not be bounded below away from zero. Thus Lemma 3.1 can be interpreted as a singular version of similar results in [8], [11].…”
Section: Proof Of Theorem 21 By Convex Integrationmentioning
confidence: 75%
See 1 more Smart Citation
“…Similarly, r need not be bounded below away from zero. Thus Lemma 3.1 can be interpreted as a singular version of similar results in [8], [11].…”
Section: Proof Of Theorem 21 By Convex Integrationmentioning
confidence: 75%
“…Chiodaroli [8] obtained similar illposedness results for the compressible Euler system using a "nonconstant" coefficient version of the method of [11]; later the method was further extended in [9] in order to attack the more complex Euler-Fourier system. The main idea, elaborated in [9], is to consider the Helmholtz decomposition…”
Section: Weak Solutionsmentioning
confidence: 86%
“…Unfortunately, this generality is also its main disadvantage. Specifically, the beautiful result of de Lellis & Szekelyhidi [1] (see in addition the recent article of Chiodaroli [9]) tells us: Theorem 4.1 seems to reject (at least in its present form) the 'thermodynamic admissibility criterion' given by inequality (3.1). What can be said for the other two?…”
Section: A Comparison Of Admissibility Criteriamentioning
confidence: 98%
“…Capillarity will penalize initial oscillations in density, viscosity will penalize oscillations in the multi-dimensional contact discontinuities which are the heart of the non-uniqueness example of Chiodaroli [9]. But there is a caveat: viscosity must be strong enough to dominate capillarity.…”
Section: Implications For Non-uniqueness Of Euler Equationsmentioning
confidence: 99%
“…On the other hand, measure-valued solutions have been criticized for being too weak, as is apparent from their obvious non-uniqueness (but see the weak-strong uniqueness results in [2,14]). However, recent results by the first three authors jointly with De Lellis [3,4,5] have demonstrated that for the compressible Euler equations (1.1) even entropy solutions (weak solutions satisfying a suitable entropy inequality) may not be unique, thus raising anew the problem of a correct notion of solutions for (1.1).…”
Section: Introductionmentioning
confidence: 99%